Criminal System Against Corporation in Corporate Crime Based on Justice - Elsi Elvina; M. Musa (International Conference On Law And Social Sciences, 2024)
Provisions regarding the punishment of corporations are not regulated in the Criminal Code, but are contained in several special laws and regulations and the National Criminal Code, namely Law Number 1 of 2023. The corporation itself has a very important role in today's modern era, because the importance of corporations makes the administrators end up using all means to get profits and commit criminal acts. As a result of criminal acts committed by the administrators resulting in losses to the community. Corporations in special laws and the national Criminal Code have designated corporations as criminal subjects. The problem in this article is how the system of punishment against corporations in corporate crime is based on justice and how the system of punishment against corporations in various countries. This research is a normative research by approaching laws and regulations, analysis and legal comparison. From the discussion, it can be concluded that corporations can be subject to criminal law in several laws and regulations outside the Criminal Code which are included in special crimes and in the national Criminal Code The corporate legal responsibility system is divided into: management as maker and as person in charge, corporation as maker and responsible manager, corporation as maker and as person in charge and manager and corporation as non-criminal offender and Both are responsible